Vloga gensko spremenjenih organizmov v sodobnem afriškem kmetijstvu - Vintar Mally, Katja (Družboslovne razprave, 2011)
The article evaluates the present and possible future role of genetically modified organisms in the agricultural production of African countries. It also addresses their potential impacts on the environment and the socio-economic status of subsistence African farmers. South Africa, Burkina Faso and Egypt are the only African countries that are commercially producing genetically modified crops. Several other countries are reporting field trials or the availability of research capacities. In the last few years, the majority of African countries have received food aid that is often genetically modified. Due to health and environmental concerns, several countries have rejected such aid and triggered reforms of international food aid policies. The article presents the main legal responses to the introduction of genetically modified organisms and some possibilities for achieving food security, taking the projected effects of climate change and population growth into account.
Keywords: Gensko spremenjeni organizmi; Transgenic organisms; Hrana; Food; Kmetijstvo; Agriculture; Africa; Afrika; gensko spremenjena hrana